PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA KONSUMEN KLINIK ERHA DI MALANG) - Alviska, Amalia Reva (Manajemen Bisnis, 2017)
This study aimed at analyzing and testing the effect of product and service quality and trust over consumers of Erha Clinic Malang. Method applied in this study was by survey. The analysis tool was double linear regression and hypothetical test by using t-test. Result of the study showed that the product and service quality and trust had a partial effect on consumer loyalty. Based on result and discussion of the study, it was concluded that the performance, endurance, attraction and quality being perceived affected significantly toward the consumers? loyalty. While the physical evidence, reliability, responsiveness, assurance and empathy effected significantly toward the consumers? loyalty. The goodness, competence had significant effect toward the loyalty of Erha Clinic Malang.